The Effect of Indonesian-Language Chatbot Interface Design on User Experience in an Academic Writing Practice Platform in Higher Education - Johar Amir; Ambo Dalle; Alamsyah; Sabrina Saiidi (Academic Bright Collaboration, 2025)
Purpose – Academic writing proficiency remains a persistent challenge for university students in Indonesia. This study investigates whether differences in the user interface (UI) design of an Indonesian-language chatbot - specifically a formal/minimalist design versus a conversational/feature-rich design - produce significant differences in user experience (UX) within an academic writing practice platform at the higher education level. Methods – A quasi-experimental design was employed with 30 undergraduate students divided into two groups of 15. Participants interacted with their assigned chatbot interface across four writing sessions. Data were collected using the System Usability Scale (SUS), the User Experience Questionnaire (UEQ), and a domain-specific seven-item Chatbot Response Quality instrument developed for the Indonesian academic writing context. Between-group differences were analysed using the Mann-Whitney U non-parametric test (α = .05). Findings – The conversational/feature-rich design (Design B) significantly outperformed the formal/minimalist design (Design A) on overall usability (Mean SUS: 88.17 vs. 72.67; p = .002), four of six UEQ dimensions - Attractiveness (p = .018), Perspicuity (p = .041), Stimulation (p = .001), and Novelty (p < .001) - and Indonesian-language chatbot response quality (p = .003). No significant differences were found in UEQ Efficiency (p = .058) or Dependability (p = .237). Research implications – Findings are based on a small single-institution sample (n = 15 per group), limiting generalisability. The domain-specific instrument has not yet undergone full psychometric validation. Results may not transfer uniformly across Indonesia's diverse regional and institutional contexts. Originality – This study is among the first to experimentally compare chatbot interface design variants within an Indonesian-language academic writing context and to develop a domain-specific UX instrument tailored to this setting. The findings provide empirical and actionable design guidelines for developers of Indonesian-language educational chatbots, and establish a replicable research framework for further cross-institutional and longitudinal investigation.